One-Stop Noodles Sdn. Bhd / Raja Yusnizam Raja Md Yusop ... [et al.] - Raja Md Yusop, Raja Yusnizam; Jaafar, Iskandar; Mohd Ismail, Nora Hakimi; Johari, Johana; Said, Nor Azira (2001)
As we see it, business is one of the major sources of income for human since the early ages of civilization. And the up and down of certain civilization as history told us, has shown that business in the food industries has a big potential to increase someone wealth and giving a boost to their lifestyle and living. That bring about why we choose to jump ahead into this business. As in our point of view our business is new to the people here and as we know it Malaysian people like to test a new venture like what we're giving them, one-stop noodle house. Which are our specialties is in only serving mainly on noodle dishes. After a while research in this field we found out that only Chinese has dominated the area exceeding other races where it is our target market will be. Which our operation places will be in Midlands Shopping Centre , Pulau Tikus ,Pulau Pinang . From the research we found that area is highly populated with Chinese mainly. Malays and others which are oriented to try out new eating place such as our own. From this, we hope to have a profitable business like other business in that area. As our business provides consumer three main style of cooking noodles for them . First , style of cooking it was by frying the noodle .second way of cooking the noodle is with soup and the fastest way of cooking it is Noodles with add in only . We hope from this three ways of cooking , we will give various choice of taste and style for serving it. which our restaurant in our view shows the interior environment to give the customer an exclusive feeling when they walk into our place . which for instance our place will be decorated with perfect lighting and the wall will be decorated with bottles fill with noodles from various kind and shape.to create a mood for our customer to choose the type of noodle they want and how they like it. Hoping from this , our business will bring reasonable profit for us that will be divided equally among the partners according to the partnership agreement. Most likely for any new business like us the first and second year usually doesn't generate satisfying income for the partners , yet we still can cover all the expenses needed and still survive in this industry. As any Muslims knows 1/3 of the wealth for business comes from food industry .According to this we believe to stand out high continuing our business.